Roof integrated photovoltaic for electric vehicle charging towards net zero residential buildings in Australia - Khan, Sanjay; Sudhakar, K.; Mohd Hazwan, Yusof; Wan Azmi, Wan Hamzah; Ali, Hafiz Muhammad (Elsevier, 2023)
The residential building sector & transportation sector has received significant attention in recent years due to carbon emissions affecting the livelihoods of humans. Electric vehicles (EVs) are poised to play a vital role in reducing dependency on non-renewable fuels and the transportation sector's environmental implications. Building integrated Photovoltaics (BIPV), on the other hand, will be able to cut down the energy requirements and contribute to building sustainability. This paper evaluates the energy, economic, and environmental performances of BIPV with EV charging system systems for a building in Canberra, Australia. BIPV with EV charging can assist in fulfilling building energy needs, charging electric vehicles, and reducing grid reliance. Different load scenarios were studied to optimize system size. Different panel layouts with orientation have been studied for the 5.0kWp BIPV system, each module rating 355kWp. The annual energy output of the BIPV system was found to vary between 8.56 MWh for layout one and 7.08MWh for layout 3. It was found that the payback back of the proposed BIPV system is 4.46 years, LCOE of 0.074AUD/kWh and EV charging cost of 0.95AUD/100 km. The BIPV with EV charging system could save approximately 160,198 kgCO2e in GHG emissions over its lifespan.